Expression of Quality Early Childhood Education of Children Deprived of Parental Care - Mazolevskienė, Aldona; Morkvėnienė, Judita (Pedagogika, 2016)
The article presents discusses issues of relevant and almost not analysed quality early childhood education of children deprived of parental care in Lithuanian and abroad. Scientific literature states, that children living in foster homes, as well as children growing in two-parent families, have the same opportunities to quality development. To reveal the scientific problem, the following aim of the research occurs, i.e. theoretically ground and empirically examine the expression of quality early childhood education of children deprived of parental care by creating a quality education model for children deprived of parental care. After summarizing the data of foster homes principals’ survey it was noticed, that leaders of foster homes are oriented towards the ensuring the access of quality early childhood education. However, foster homes do not follow contemporary Lithuanian and foreign standards of early childhood education. Qualitative research revealed, that highlight quality early childhood education determinants while identifying it’s implementing issues occurring in foster homes.